Bold, Brave, and Proactive: Advocacy and Organizing at the Intersection of Reproductive Justice and LGBTQ Liberation - Gonzalez-Rojas, Jessica (Columbia Journal of Gender and Law, 2015)
The National Latina Institute for Reproductive Health (NLIRH) is the only national reproductive justice organization dedicated to building Latina power to advance health, dignity, and justice for 25 million Latinas, our families, and communities in the United States. We do this through leadership development, community mobilization, policy advocacy, and strategic communications.